URGENT NEED TO FORM A TASK FORCE TO END BULLYING IN SCHOOLS - Permanasari, Ai (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2024)
School should be a safe place for children to get an education and develop themselves optimally, but violence often occurs in the educational environment itself, one of which is bullying. Research shows that eradicating bullying is the work of all parties, the government, schools, parents, including students. Because bullying in schools occurs in the school environment both inside and outside of school, or online, the biggest initiative is the availability of equipment to address bullying in the school institution. As an implementation of the Regulation of the Minister of Education and Culture Number 46 of 2023 concerning the Prevention and Handling of Violence in the Educational Unit Environment, an anti-violence/bullying Task Force Team must be formed in educational institutions. However, in its implementation, many schools still do not have this team, and even if they do have it, their performance is still not optimal.